2021
DOI: 10.1186/s12939-021-01428-z
|View full text |Cite
|
Sign up to set email alerts
|

Changing men or changing health systems? A scoping review of interventions, services and programmes targeting men’s health in sub-Saharan Africa

Abstract: Background Sex and gender have been shown to influence health literacy, health seeking behaviour, and health outcomes. However, research examining the links between gender and health has mainly focused on women’s health, which is a long-standing global health priority. We examine literature focused on the ‘missing men’ in global health research, in particular empirical studies that document interventions, programmes, and services targeting men’s health issues in Sub-Saharan Africa. Within these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 84 publications
0
36
1
4
Order By: Relevance
“…This subsequently negatively affected male engagement and exacerbated a perception by both potential and current male clients of CHIEDZA as a female-only service. These findings build on existing evidence highlighting poor male engagement with SRH services and the need for health systems to consider men’s perceptions of health services and how this informs health-seeking behaviours [ 33 ].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This subsequently negatively affected male engagement and exacerbated a perception by both potential and current male clients of CHIEDZA as a female-only service. These findings build on existing evidence highlighting poor male engagement with SRH services and the need for health systems to consider men’s perceptions of health services and how this informs health-seeking behaviours [ 33 ].…”
Section: Discussionmentioning
confidence: 78%
“…Overall, the study results showed that the MHH intervention itself and its integration within an SRH community-based service were acceptable among both intervention implementors and young women in communities across Zimbabwe. In an environment where there is a global push for the integration of MHH and SRH and uptake of SRH services is especially low amongst men [ 33 ], our findings add to the increasing evidence base for integrated services and provide crucial insight into some of the contextual factors policy-makers and implementors should consider and pre-emptively prepare for when designing and implementing acceptable integrated SRH services in community-based settings. Acceptable MHH interventions need to be comprehensive and need to consider the contextual factors that inform access to and informed choice of menstrual products [ 18 , 28 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 79%
“…However, men compared to women were less likely to have vaccinated (63% vs.73%) or willing to vaccinate (30% vs.25%). Men are known to less likely seek medical services than women in SSA) [34,35]. According to the World Health organization, vaccine acceptance is influenced by a constellation of factors including confidence, complacency, and convenience [14,26].…”
Section: Discussionmentioning
confidence: 99%
“…Gender-transformative interventions and research in the Global South, however, are showing that unjust systems can be changed. 9 Furthermore, successful gender-transformative interventions do not just require action from government bodies, as the EUPHA statement 1 remarks. Instead, it takes sustained action and strategic co-operation between governments, activists, health providers, civic society associations and research institutions that hold themselves and each other accountable in mobilizing their forces within and across their respective levels.…”
mentioning
confidence: 99%
“…Instead, it takes sustained action and strategic co-operation between governments, activists, health providers, civic society associations and research institutions that hold themselves and each other accountable in mobilizing their forces within and across their respective levels. 9 …”
mentioning
confidence: 99%